Wyobraźnia eschatologiczna. Dialog z antyczną tradycją w I księdze poematu "Crisias" Hilariona z Werony - Janus, Katarzyna Joanna (Verbum Vitae, 2021)
In this article an attempt is made to analyze and interpret the first book of the epos Crisias, by Hilarion of Verona. The purpose of the article is to identify and illuminate the ancient literary, historical and mythological sources used by that author to fashion an eschatological imagination. According to the thesis presented in this article, contextual references in Crisias constituted a path of communication between the writer, Hilarion of Verona, and the reader, Bessarion. Hilarion of Verona is an otherwise unknown writer of the Italian quattrocento, therefore a presentation of the intellectual environment within which that author operated is a necessary part of our analysis. The reflection offered in this paper can be treated as a prolegomena to further research, since the epos Crisias has never before been the focus of research within Polish scholarship.